Beyond the Extra Respiration of Phagocytosis: NADPH Oxidase 2 in Adaptive Immunity and Inflammation - Mortimer, Paige M.; Mc Intyre, Stacey A.; Thomas, David C. (Frontiers in Immunology, 2021)
Reactive oxygen species (ROS) derived from the phagocyte NADPH oxidase (NOX2) are essential for host defence and immunoregulation. Their levels must be tightly controlled. ROS are required to prevent infection and are used in signalling to regulate several processes that are essential for normal immunity. A lack of ROS then leads to immunodeficiency and autoinflammation. However, excess ROS are also deleterious, damaging tissues by causing oxidative stress. In this review, we focus on two particular aspects of ROS biology: (i) the emerging understanding that NOX2-derived ROS play a pivotal role in the development and maintenance of adaptive immunity and (ii) the effects of excess ROS in systemic disease and how limiting ROS might represent a therapeutic avenue in limiting excess inflammation.